Postoperative microcystic meningioma of the fourth ventricle with subsequent giant cell reparative granuloma: a case report - Xu, Fangfang; Fu, Chengzhi; Li, Qian; Dong, Fei; Tang, Jinlong; Wang, Chao; Sun, Chongran (Frontiers in Oncology, 2025)
BackgroundMicrocystic meningioma (MM) is a distinctive benign tumor typically located in the supratentorial region. Giant cell reparative granuloma (GCRG) is another rare reactive benign lesion associated with surgical trauma or tissue injury. The occurrence of MM in the fourth ventricle is extremely uncommon, and the development of GCRG following cranial tumor surgery is rare.Case report: We present a case of MM extending into the fourth ventricle in a 54-year-old man. The initial diagnosis was based on magnetic resonance imaging (MRI), and the tumor was successfully treated with surgery. Postoperative histopathological analysis confirmed the diagnosis of MM. However, a mass was detected at the original surgical site during a follow-up examination one year later. Combined preoperative imaging and postoperative pathology confirmed the final diagnosis of giant cell reparative granuloma (GCRG).ConclusionIn cases of MM at atypical locations and GCRG, an imaging-based differential diagnosis is crucial for guiding treatment decisions and predicting prognosis. Regular postoperative reviews are also essential for detecting complications.